I = ∫ 0 e 1 − ln ( x ) d x
If the above integral can be expressed in the form A e B π C for rational numbers A , B , and C , find A + B + C .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = 1 − ln ( x )
First, we notice that f ( x ) is strictly decreasing in its domain. Therefore, f ( x ) has an inverse function f − 1 ( x ) , which can be easily found to be f − 1 ( x ) = e 1 − x 2
If we look at our integral in the plane, we see that
I = ∫ 0 e f ( x ) d x = − ∫ f ( 0 ) f ( e ) f − 1 ( y ) d y = ∫ 0 ∞ e 1 − y 2 d y
We can rewrite the last form for I as follows;
I = e ∫ 0 ∞ e − y 2 d y
Which contains the well known Gaussian Integral. Therefore, I = 2 e π and we can obtain our final answer of 2 1 + 1 + 2 1 = 2
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 0 e 1 − ln ( x ) d x
l e t u = 1 − ln ( x ) ⇒ x = e ( 1 − u ) ⇒ d x = − e ( 1 − u ) d u
I = ∫ 0 ∞ u 2 1 e ( 1 − u ) d u = e ∫ 0 ∞ u 2 1 e − u d u
I = e ⋅ Γ ( 2 3 ) = e ⋅ 2 1 ⋅ Γ ( 2 1 ) Gamma Function
I = 2 1 e π
A = 2 1 , B = 1 , C = 2 1
A + B + C = 2